LEG MUSCLE EXPLOSIVE POWER AND THE SPEED OF KICKING MAWASHI GERI - Pangondian Hotliber Purba (Jambura Journal of Sports Coaching, 2019)
This study aims to determine the relationship between leg muscle explosive power and the speed of kicking mawashi geri in Unimed special karateka athletes wadokai dojo. The research method used in this study is a simple correlation. The research subjects were 27 Unimed male and female athletes wadokai dojo, which were the study samples. The test instrument used to measure the explosive power of the limb muscles is the standing broad jump test and to measure the speed of the kicking mawashi geri is to use the ulead audio video with the help of 2 sempai (karate experts). The results showed that there was a significant relationship between the explosive power of the leg muscles against the speed of the kicking of the mawashi geri in the athletes of the wadokai dojo specifically. The results of the study, obtained t count of 3.05 and t table of 1.708 at the level of confidence ? = 0.05. Thus, t count t table then the hypothesis Ha is accepted and Ho is rejected. Furthermore, the determinant coefficient of limb muscle explosive power on the speed of mawashi geri in the karateka was obtained 0.2704, this means that the explosive power of limb muscles plays a role in the results of mawashi geri kicking of 27.04% and the remaining 72.96% mawashi geri kicking ability influenced by other factors such as agility, speed, flexibility, strength.